Immunogenicity of a Bivalent Adjuvanted Glycoconjugate Vaccine against Salmonella Typhimurium and Salmonella Enteritidis - Fiorino, Fabio; Rondini, Simona; Micoli, Francesca; Lanzilao, Luisa; Alfini, Renzo; Mancini, Francesca; MacLennan, Calman A.; Medaglini, Donata (Frontiers in Immunology, 2017)
Salmonella enterica serovars Typhimurium and Enteritidis are the predominant causes of invasive non-typhoidal Salmonella (iNTS) disease. Considering the co-endemicity of S. Typhimurium and S. Enteritidis, a bivalent vaccine formulation against both pathogens is necessary for protection against iNTS disease, thus investigation of glycoconjugate combination is required. In the present work, we investigated the immune responses induced by S. Typhimurium and S. Enteritidis monovalent and bivalent glycoconjugate vaccines adjuvanted with aluminum hydroxide (alum) only or in combination with cytosine-phosphorothioate-guanine oligodeoxynucleotide (CpG). Humoral and cellular, systemic and local, immune responses were characterized in two different mouse strains. All conjugate vaccines elicited high levels of serum IgG against the respective O-antigens (OAg) with bactericidal activity. The bivalent conjugate vaccine induced systemic production of antibodies against both S. Typhimurium and S. Enteritidis OAg. The presence of alum or alum + CpG adjuvants in vaccine formulations significantly increased the serum antigen-specific antibody production. The alum + CpG bivalent vaccine formulation triggered the highest systemic anti-OAg antibodies and also a significant increase of anti-OAg IgG in intestinal washes and fecal samples, with a positive correlation with serum levels. These data demonstrate the ability of monovalent and bivalent conjugate vaccines against S. Typhimurium and S. Enteritidis to induce systemic and local immune responses in different mouse strains, and highlight the suitability of a bivalent glycoconjugate formulation, especially when adjuvanted with alum + CpG, as a promising candidate vaccine against iNTS disease.